Self-Assembled monolayers with embedded dipole moments for work function engineering of oxide substrates - Asyuda, Andika; Gärtner, Michael; Wan, Xianglong; Burkhart, Ines; Saßmannshausen, Torben; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
Self-assembled monolayers (SAMs) are frequently used for work function (WF) engineering of different materials. For this, typically dipolar groups are attached to the molecule terminus at the SAM-ambient interface, which also influences its chemistry. WF engineering and interface chemistry can, however, be decoupled from one another using embedded dipolar groups, as has been demonstrated before for thiolate SAMs on metals. Herein, we extend this concept to oxide substrates. For this, a series of biphenyl-based molecules with a phosphonic acid (PA) anchoring group was synthesized, with one of the nonpolar phenyl units exchanged for a polar pyrimidine moiety, the dipole moment of which is oriented either toward (“down”) or away (“up”) to/from the PA group and, consequently, to/from the substrate. SAMs of these molecules formed on indium tin oxide (ITO), a frequently used and application-relevant oxide substrate, feature a uniform molecular configuration, dense molecular packing, and an upright molecular orientation. These SAMs exhibit pronounced electrostatic effects associated with the embedded dipolar groups, viz. shifts of the characteristic peaks in the C 1s X-ray photoelectron spectra and WF variations. The latter values were found to be 3.9, 4.85, and 4.4 eV for the up, down, and nonpolar reference SAM-engineered ITO, respectively. Consequently, these SAMs can serve as a powerful tool to monitor WF engineering effects in a variety of device assembles, decoupling these effects from the interface chemistry. The comparably low WF value for the up SAM is particularly important since it extends a rather limited variety of SAMs capable of lowering the WF of ITO.